The structure of tagetitoxin. Issue 1 (30th October 2015) - Aliev, Abil E.; Karu, Kersti; Mitchell, Robin E.; Porter, Michael J.
Abstract : The previously reported structure of tagetitoxin is incorrect. A new structure of tagetitoxin is proposed based on the NMR analysis. Abstract : Based on detailed analysis of newly acquired NMR data, we show that the previously revised structure of tagetitoxin is incorrect. A new structure of tagetitoxin is proposed which is consistent with the NMR and MS data.